Study of Reducing Transmission Losses in Java-Bali System with the Addition of Capacitors along with Optimal Capacitor Placement Methods Using Quasi-Dynamic Simulation - Ali, Haidar; Sudiarto, Budi; Jufri, Fauzan Hanif; Salile, Ahmad Yusuf; Nasution, Eldi Firmansyah; Marbun, M (Universitas Indonesia, 2024)
The Java-Bali electricity system is the largest electricity system in Indonesia which consists of 5 areas including Jakarta-Banten area, West Java area, Central Java area, East Java area and Bali area. This system is operated to meet the economic, reliability, quality, and green principles. In the case of reliability, one of the essential aims is minimization of transmission losses due to importance in system improvement to increase system operational efficiency to the possible extent. Transmission losses are an inevitable part of the electric power transfer process from generation stations to consumers. The power losses in a transmission line are inversely proportional to the square of the line voltage. This implies that lower line voltages result in higher power losses. Therefore, it is crucial to maintain optimal voltage levels to minimize transmission losses and ensure efficient energy delivery across the power system. One effective way to achieve this is by integrating capacitors into the system. In this study, we have explored two methods that aim to pinpoint the most advantageous locations for the integration of new capacitors. The goal is to optimize capacitor planning, with an emphasis not only on improving voltage levels but also on minimizing transmission losses within the Java-Bali system. The research results indicate that implementing two proposed methods can significantly reduce transmission losses in The Java-Bali system. Method-1 involves identifying the lowest voltage over the course of a year, while Method-2 focuses on the lowest voltage value within the first quartile (Q1/25%) during the same period